EFFECTS OF FLOODS AND TORRENTS ON HUMAN LIFE - Korkanç, Selma Yaşar; Korkanç, Mustafa (Bartın Üniversitesi, 2006)
Floods and torrents are common natural disasters and cause important economic damages in the environment and create very serious health problems in human life. Despite these problems, effects of flood and torrents on human health have not been assessed adequately, especially in Turkey. Accurate data related with these natural disasters from the beginning of the floods and torrents to the end of these events are needed to determine their effect on human life including deaths, injures, diseases, etc. Some structural and non-structural measures should be taken into account to prevent and/or reduce these hazards. In this study, effects of floods and torrents on human life and what should be done to reduce flood hazards are discussed.

Taşkın ve seller geçmişten beri önemli miktarda maddi ve manevi zararlara neden olmaktadır. Yaygın bir doğal afet olmasına karşın sel ve taşkınların insan sağlığı üzerindeki etkileri özellikle ülkemizde yeterli şekilde değerlendirilmemiştir. Bu doğal afetlerin neden olduğu zararlarla ilgili sağlıklı veri eksikliği söz konusudur. Sel ve taşkınları insan hayatı üzerindeki en önemli etkileri ölüm, yaralanmalar, sel sonrası meydana gelen hastalıklar vb. şeklinde kendini göstermektedir. Bu zararların azaltılması için sel öncesinde, sırasında ve sonrasında birtakım yapısal ve yapısal olmayan önlemler alınması gereklidir. Bu çalışmada sel ve taşkın olaylarının insan hayatı üzerindeki etkileri ve bu etkileri azaltmak için neler yapılması gerektiği irdelenmiştir.
SEL VE TAŞKINLARIN İNSAN HAYATI ÜZERİNDEKİ ETKİLERİ